Oral microbiomes from hunter‐gatherers and traditional farmers reveal shifts in commensal balance and pathogen load linked to diet. Issue 1 (14th December 2017) - Lassalle, Florent; Spagnoletti, Matteo; Fumagalli, Matteo; Shaw, Liam; Dyble, Mark; Walker, Catherine; Thomas, Mark G.; Bamberg Migliano, Andrea; Balloux, Francois
Abstract: Maladaptation to modern diets has been implicated in several chronic disorders. Given the higher prevalence of disease such as dental caries and chronic gum diseases in industrialized societies, we sought to investigate the impact of different subsistence strategies on oral health and physiology, as documented by the oral microbiome. To control for confounding variables such as environment and host genetics, we sampled saliva from three pairs of populations of hunter‐gatherers and traditional farmers living in close proximity in the Philippines. Deep shotgun sequencing of salivary DNA generated high‐coverage microbiomes along with human genomes. Comparing these microbiomes with publicly available data from individuals living on a Western diet revealed that abundance ratios of core species were significantly correlated with subsistence strategy, with hunter‐gatherers and Westerners occupying either end of a gradient of Neisseria against Haemophilus, and traditional farmers falling in between. Species found preferentially in hunter‐gatherers included microbes often considered as oral pathogens, despite their hosts' apparent good oral health. Discriminant analysis of gene functions revealed vitamin B5 autotrophy and urease‐mediated pH regulation as candidate adaptations of the microbiome to the hunter‐gatherer and Western diets, respectively. These results suggest that major transitions in diet selected for different communities of commensals and likely played a role in the emergence of modern oral pathogens.